Clinical outcome of sorafenib treatment in patients with advanced hepatocellular carcinoma refractory to hepatic arterial infusion chemotherapy. Issue 12 (December 2013) - Miyaki, Daisuke; Aikata, Hiroshi; Kan, Hiromi; Fujino, Hatsue; Urabe, Ayako; Masaki, Keiichi; Fukuhara, Takayuki; Kobayashi, Tomoki; Naeshiro, Noriaki; Nakahara, Takashi; Kawaoka, Tomokazu; Hiramatsu, Akira; et al.
Abstract Background and Aim It has been reported about poor prognosis in patients with advanced hepatocellular carcinoma (HCC) refractory to hepatic arterial infusion chemotherapy (HAIC). We assessed the survival benefits of sorafenib therapy for advanced HCC in HAIC refractory patients. Methods The study subjects were 191 patients with advanced HCC who had been treated with HAIC. Sorafenib was used in 27 patients who finally failed to respond to HAIC (HAIC/sorafenib group). Clinical outcome was compared between HAIC/sorafenib and HAIC alone groups. Results There were no significant differences in clinical characteristics and response rate of HAIC between the two groups (response rate: 25.9%, HAIC/sorafenib group; 30.4%, HAIC alone group). The median survival time (MST) for all patients was 11.0 months. The survival rate was significantly higher in the HAIC/sorafenib group than HAIC alone group (MST 22.2 vs 8.7 months, P = 0.017). From administration sorafenib, the disease control rate was 51.8% with MST of 10.4 months. Among HAIC non‐responders, the survival rate was significantly higher in the HAIC/sorafenib group than HAIC alone group. Multivariate analysis identified additional therapy with sorafenib as significant and independent determinant of overall survival in all patients and HAIC non‐responders. Conclusion Additional therapy with sorafenib could probably improve the prognosis of HAIC refractory patients.